1985
DOI: 10.1017/s0022112085003226
|View full text |Cite
|
Sign up to set email alerts
|

Optimal discharge profiles for sudden contaminant releases in steady, uniform open-channel flow

Abstract: The effect of varying the initial concentration distribution is investigated for a sudden contaminant release in a uniform straight channel. Taking the optimal choice to be that which maximizes the variance of the contaminant cloud far downstream, it is found that, unless the topography is very unusual, the largest variance can be generated by splitting the contaminant into two parts, placing the larger part at the bank where the channel bed slopes most gently, and the remainder near to where the channel is de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The depth-linked formulae (11) ensure that in the deepest parts of the channel the velocity is greatest and transverse mixing is most vigorous [2]. It is implicit that the pollutant is sufficiently dilute that it does not significantly modify the turbulence (e.g.…”
Section: Flow Parameters In Straight Channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The depth-linked formulae (11) ensure that in the deepest parts of the channel the velocity is greatest and transverse mixing is most vigorous [2]. It is implicit that the pollutant is sufficiently dilute that it does not significantly modify the turbulence (e.g.…”
Section: Flow Parameters In Straight Channelsmentioning
confidence: 99%
“…In the context of pollution minimisation from sudden discharges of pollutants, Daish [2] used piecewise linear depth profiles to construct a wide range of test problems. The following three sub-sections concern the linear depth profile (15), but with decay profiles corresponding to uniform consumption by bacteria, to evaporation and to break up by turbulence.…”
Section: Linearly Increasing Depthmentioning
confidence: 99%
“…For steady flows in rivers Smith (1981Smith ( , 1984 and Daish (1985) have shown that the cross-stream location of an instantaneous contaminant release can have a persistent and marked effect upon the concentrations experienced far downstream ; while, for uniform discharges in oscillatory flows, Allen (1982, figure 8) and Smith (1982, figures 2a-c) have drawn attention to the importance of the timing of the contaminant release. The purpose of the present paper is to encompass both these features and to investigate the long-term influence of the precise timing and cross-stream position of a discharge in an oscillatory flow.…”
Section: Introductionmentioning
confidence: 99%